Cognitive Fatigue and Its Relationship to Academic Self-Efficacy among University Students - Muhammad, Sarab Abdel Sattar (Journal of Tikrit University for Humanities, 2025)
The current research aims to identify Cognitive fatigue among university students. Academic self-efficacy among university students. Statistically significant differences in cognitive fatigue and academic self-efficacy according to the gender variable (males, females). The correlation between cognitive fatigue and academic self-efficacy among university students The researcher applied the research tools to a sample of Tikrit University students consisting of (300) male and female students. The number of males (177) and females (123) were from scientific and humanities specializations, and they were selected randomly. The researcher adopted the (Penner, Atel, 2005) scale for cognitive fatigue, which was translated into Arabic by specialists and prepared by (Saud, 2023), and after extracting the psychometric properties of the scale, such as validity, reliability, and discrimination, the items of the scale in its final form included (20) items. The researcher prepared a scale (Al-Lami, 2023) for academic self-efficacy, and after extracting the psychometric properties, the scale became in its final form (36) items. To achieve the research objectives, the researcher used the following statistical methods: (t-test for one sample, t-test for two independent samples, chi-square, Pearson correlation coefficient, Cronbach’s alpha equation). The results of the current research found that Tikrit University students do not have a level of cognitive fatigue and have academic self-efficacy, and there are no statistically significant differences depending on the gender variable (males- females) for the two variables. It also concluded that there is an inverse and significant correlation between cognitive fatigue and academic self-efficacy. In light of the results, the researcher presented a number of recommendations and proposals.